Magnetic Nanoparticles: Advances in Synthesis, Sensing, and Theragnostic Applications - Adeyemi O. Adeeyo; Mercy A. Alabi; Joshua A. Oyetade; Thabo T. I. Nkambule; Bhekie B. Mamba; Adewale O. Oladipo; Rachel Makungo; Titus A. M. Msagati (Magnetochemistry)
The synthesis of magnetic nanoparticles (MNPs) via the chemical, biological, and physical routes has been reported on along with advantages and attendant limitations. This study focuses on the sensing and emerging theragnostic applications of this category of nanoparticles (NPs) in clinical sciences by unveiling the unique performance of these NPs in the biological sensing of bacteria and nucleotide sequencing. Also, in terms of medicine and clinical science, this review analyzes the emerging theragnostic applications of NPs in drug delivery, bone tissue engineering, deep brain stimulation, therapeutic hyperthermia, tumor detection, magnetic imaging and cell tracking, lymph node visualization, blood purification, and COVID-19 detection. This review presents succinct surface functionalization and unique surface coating techniques to confer less toxicity and biocompatibility during synthesis, which are often identified as limitations in medical applications. This study also indicates that these surface improvement techniques are useful for refining the selective activity of MNPs during their use as sensors and biomarkers. In addition, this study unveils attendant limitations, especially toxicological impacts on biomolecules, and suggests that future research should pay attention to the mitigation of the biotoxicity of MNPs. Thus, this study presents a proficient approach for the synthesis of high-performance MNPs fit for proficient medicine in the detection of microorganisms, better diagnosis, and treatment in medicine.